The deposit slopes at the Cerro Divisadero torrents, Coyhaique, Chile - Iroume A., Andrés; Gayoso A., Jorge (Bosque (Valdivia), 1991)
The deposit bed slopes produced by the control structures built at the Cerro Divisadero torrents were studied. All the observed deposit slopes were found to be larger than que slope used for torrent control structure and systems design, which was estimated using empirical models. 30 channel profiles, taken upstream from check dams at Los Coigües and Los Saltos torrents were analyzed. In these profiles, equilibrium slopes were significantly correlated with the original stream bed slopes. The fitted equations can be used to estimate deposit slopes for other torrent control projects in the area. These equations need to be verified in the future.